PERAN WORK LIFE BALANCE TERHADAP WORK ENGAGEMENT PADA KARYAWAN WANITA MENIKAH PADA BANK ABC CABANG MEDAN - Fahmi Sulaiman; Jihan Sulaiman; Amarisma Gusria (Smart Education, 2025)
Abstract: This study aims to determine the role of work-life balance on work engagement among married female employees at Bank ABC Medan Branch. The population in this study consisted of 55 employees. Sampling in this study was conducted using total sampling technique, where the entire population became the sample. This study used a quantitative approach. The instruments used were validated and reliable work-life balance and work engagement questionnaires. The data were analyzed using simple regression analysis. The results indicate that work-life balance plays a role in work engagement, with a calculated F value of 62.276 > table F value of 4.03 and a significance level of 0.000 (p < 0.05).. Keyword: work life balance; work engagement; bank; employee; medan Abstrak: Penelitian ini bertujuan untuk mengetahui peran work life balance terhadap work engagement Pada Karyawan Wanita Menikah Pada Bank ABC Cabang Kota Medan. Populasi dalam penelitian ini adalah 55 karyawan. Pengambilan sampel dalam penelitian ini dengan teknik total sampling, dimana seluruh populasi yang menjadi sampel. Penelitian menggunakan pendekatan kuantitatif. Instumen yang digunakan adalah angket work life balance dan work engagement yang telah valid dan reliabel. Penelitian ini dianalisis dengan uji analisi regresi sederhana. Hasil penelitian menunjukkan bahwa Ada peran work life balance terhadap work engagment dengan F hitung = 62.276 > nilai F tabel = 4.03dengan nilai signifikansi 0.000 (p< 0.05). Kata kunci: work life balance, work engagement